Estimation of the Mitochondrial Membrane Potential Using Fluorescence Lifetime Imaging Microscopy. Issue 5 (5th September 2019) - Okkelman, Irina A.; Papkovsky, Dmitri B.; Dmitriev, Ruslan I.
Abstract: Monitoring of cell metabolism represents an important application area for fluorescence lifetime imaging microscopy (FLIM). In particular, assessment of mitochondrial membrane potential (MMP) in complex three‐dimensional multicellular in vitro, ex vivo, and in vivo models would enable improved segmentation and functional discrimination of cell types, directly report on the mitochondrial function and complement the quenched‐phosphorescence detection of cellular O2 and two‐photon excited FLIM of endogenous NAD(P)H. Here, we report the green and orange‐emitting fluorescent dyes SYTO and tetramethylrhodamine methyl ester (TMRM) as potential FLIM probes for MMP. In addition to nuclear, SYTO 16 and 24 dyes also display mitochondrial accumulation. FLIM with the culture of human colon cancer HCT116 cells allowed observation of the heterogeneity of mitochondrial polarization during the cell cycle progression. The dyes also demonstrated good performance with 3D cultures of Lgr5‐GFP mouse intestinal organoids, providing efficient and quick cell staining and compatibility with two‐photon excitation. Multiplexed imaging of Lgr5‐GFP, proliferating cells (Hoechst 33342‐aided FLIM), and TMRM‐FLIM allowed us to identify the population of metabolically active cells in stem cell niche. TMRM‐FLIM enabled to visualize the differences in membrane potential between Lgr5‐positive and other proliferating and differentiated cell types. Altogether, SYTO 24 and TMRM dyes represent promising markers for advanced FLIM‐based studies of cell bioenergetics with complex 3D and in vivo models. © 2019 International Society for Advancement of Cytometry Abstract : Fluorescence lifetime imaging microscopy (FLIM) enables the use of tetramethylrhodamine methyl ester and SYTO dyes as mitochondrial membrane potential‐sensing probes in live cells and organoids. Multi‐parameter FLIM visualizes mitochondrial hyperpolarization within the stem cell niche in mouse intestinal organoid model.